THERMAL ENVIRONMENT OF TIDAL MUD OF ARIAKE SEA - M. A. Moqsud; S. Hayashi; D. Suetsugu; Q. S. Bushra (Lowland Technology International, 2010)
A remarkable decrease of catch of shells was observed during the last three decades in the Ariake Sea, Japan. The higher content of acid volatile sulfide (AVS) is responsible for the unfavorable geo-environmental condition of the Ariake Sea. This paper presents an assessment of the thermal environment of the Ariake Sea tidal flat as a part of geo-environmental condition study. To observe the daily and seasonal variation of temperature in different depths, temperature was measured by inserting the thermocouple at various specified depths and at 0.10 m depths interval in the last week of every month at study areas in the Ariake Sea tidal flat, respectively. Thermal properties of the sea mud were measured by using the thermal properties analyzer (KD2). It was observed that during the spring and summer heat was transferred from subsurface to the deeper depth however during winter, and autumn the opposite phenomena happened. This type of temperature profile in the tidal flat helps to enter the sea laver treatment medicine during winter and consequently deteriorate the mud and again helped to increase remediation of the Ariake sea tidal mud naturally during summer.